The effect of captivity on craniomandibular and calcaneal ontogenetic trajectories in wild boar. Issue 8 (14th March 2022) - Neaux, Dimitri; Harbers, Hugo; Blanc, Barbara; Ortiz, Katia; Locatelli, Yann; Herrel, Anthony; Debat, Vincent; Cucchi, Thomas
Abstract: Deciphering the plastic (i.e., nonheritable) changes induced by human control over wild animals in the archeological record is challenging. Previous studies detected morphological markers associated with captivity in the cranium, mandible, and calcaneus of adult wild boar ( Sus scrofa ) but the developmental trajectories leading up to these changes during ontogeny remain unknown. To assess the impact of growth in a captive environment on morphological structures during postnatal ontogeny, we used an experimental approach focusing on the same three structures and taxon. We investigated the form and size differences of captive‐reared and wild‐caught wild boar during growth using three‐dimensional landmark‐based geometric morphometrics. Our results provide evidence of an influence of captivity on the morphology of craniomandibular structures, as wild specimens are smaller than captive individuals at similar ages. The food resources inherent to anthropogenic environments may explain some of the observed differences between captive‐reared and wild specimens. The calcaneus presents a different contrasted pattern of plasticity as captive and wild individuals differ in terms of form but not in terms of size. The physically more constrained nature of the calcaneus and the direct influence of mobility reduction on this bone may explain these discrepancies. These results provide new methodological perspectives for bioarchaeological approaches as they imply that the plastic mark of captivity can be observed in juvenile specimens in the same way it has been previously described in adults. Highlights: We showed the influence of captivity, an early step of domestication, on the morphology of craniomandibular and postcranial structures during development. It underlines the plastic nature of bony structures and their ability to change in a short time period. Abstract : Principal component (PC) analyses for the cranium in the PC1–PC2 form space.